Projecting the nation : history and ideology on the Israeli screen - Kaplan, Eran (Rutgers University Press, 2020)
"Projecting the Nation: History and Ideology on the Israeli Screen is a wide-ranging history of over seven decades of Israeli cinema. By analyzing Israeli films which address such issues as the Arab-Israeli conflict, the Ashkenazi-Mizrahi divide, the kibbutz, the rise of religion in Israel, the book explores the way cinema has represented and shaped our understanding of the Israeli history as it evolved from a collectivist society to a society where individualism and adherence to local identities is the dominant ideology"--